Anti-SARS-CoV-2 B and T-Cell Immune Responses Persist 12 Months After mRNA Vaccination with BNT162b2 in Systemic Lupus Erythematosus Patients Independently of Immunosuppressive Therapies - Mario Ferraioli; Alessandra Aiello; Immacolata Prevete; Maria Sole Chimenti; Luigi De Marco; Silvia Meschi; Davide Mariotti; Valentina Vanini; Gilda Cuzzi; Andrea Salmi; Stefania Notari; Valeria Mellini; et al. (Vaccines)
Background: In response to the SARS-CoV-2 pandemic, a massive vaccination campaign was launched. Nonetheless, concerns arose regarding some peculiar groups of patients, including those affected by Systemic Lupus Erythematosus (SLE), because of the immune-suppressive drugs routinely administered to patients and the risk of possible disease flares. Since the effects of the third booster vaccination in SLE have been poorly assessed, this study aims to evaluate the immunogenicity and safety of the third BNT162b2 vaccine dose, together with the effects of immunosuppressive drugs. Methods: A monocentric SLE cohort and a cohort of age- and sex-matched healthy controls (HCs) (all vaccinated with three homologous doses) were consecutively enrolled 6 months (T1) after their third vaccine shot. Vaccine immunogenicity was evaluated by analyzing humoral and cellular immune responses at T1 and 12 months (T2). Vaccine safety was evaluated by assessing adverse events related to vaccination (T0) and comparing disease activity among T0, T1, and T2. Effects of immunosuppressive drugs were assessed by stratifying patients according to therapy at vaccination: (1) receiving (IS) or (2) not receiving immunosuppressive drugs (Non-IS). Results: At T1, the humoral responses were comparable between SLE and HC subjects, while the cellular response was significantly higher in HC (p = 0.01). No differences were found at T2 between cohorts. Similarly, both at T1 and T2, the immune responses of IS and Non-IS groups were comparable. Moreover, lupus disease flares were limited and mostly mild, and no life-threatening adverse events were reported. Conclusions: The booster BNT162b2 vaccine is safe and induces an immune response, which is persistent and not affected by ongoing immunosuppressive drugs.